The Implementation of Liveworksheet in Teaching Capital Letters for Elementary School - Ni Kadek Dina Mei Astitiani; Anak Agung Ayu Dewi Sutyaningsih (Universitas Pendidikan Ganesha, 2025)
The lack of variety in teaching media used in learning has a negative impact on student motivation and understanding. This is certainly one of the factors that affect students' low learning outcomes. This study aims to develop e-LKPD on Indonesian language content on the use of capital letters for grade V elementary school students. This type of research is a development research using the ADDIE model. The subject of the development is e-LKPD and the object of the development is the design, validity, practicality and effectiveness of the developed e-LKPD. Data collection techniques were carried out by observation, interviews, questionnaires and multiple choice tests. The analysis methods used include quantitative descriptive analysis, qualitative, and inferential statistical analysis using paired sample t-test (dependent sample t-test). The results showed e-LKPD on Indonesian language content in the form of a website developed with Liveworksheet. The feasibility of e-LKPD is shown from the results of the learning content/material test obtained a percentage of 93.75% (very good), instructional design expert test 93.75% (very good), learning media expert test 92.5% (very good), practitioner test 93.3 (very good), individual trial 92.5% (very good), and small group trial 93.6% (very good). The t-test results obtained tcount = 16.880 and ttable = 2.064. Thus, the results of this study indicate that digital LKPD is feasible and effective in using Indonesian language content on the use of capital letters in grade V elementary school. The implication of this research is that it can improve students' understanding and support learning that is more interactive and in accordance with the development of educational technology. Therefore, teachers need to utilize e-LKPD as an innovative learning media that can support the learning process optimally.